Finite element analysis of flush end plate beam-to-column bolted steel connection on minor axis using Lusas software - 243396 Wong, Jyie Yiee; Sariffuddin Saad, supervisor; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2007